Appropriate automation of rail signalling systems: a human factors study - Balfe, Nora (2010)
This thesis examines the effect of automation in the rail signalling environment. The level of automation in a system can be described as ranging along a continuum from manual control to fully autonomous automation and development of appropriate automation for a system is likely to enhance overall system performance. Network Rail, the company which owns, operates, and maintains the rail infrastructure in the UK, envisions increasing levels of automation in future rail systems, but prior to this research, little structured evaluation of current automation had been undertaken.